Tapping the Potential of Multimodal Non-invasive Brain Stimulation to Elucidate the Pathophysiology of Movement Disorders - Shukla, Sakshi; Thirugnanasambandam, Nivethida (Frontiers in Human Neuroscience, 2021)
This mini review provides a detailed outline of studies that have used multimodal approaches in non-invasive brain stimulation to investigate the pathophysiology of the three common movement disorders namely, essential tremor, Parkinson’s disease and dystonia. Since it is now known that movement disorders are associated with altered functional connectivity in the cortical and subcortical brain networks, integrating different non-invasive brain stimulation and recording methods would be highly valuable in enhancing our understanding of their pathophysiology. Technological advancements in the field have enabled novel combinations of non-invasive brain stimulation and neuroimaging/neurophysiological methods which could have immense potential in the development of diagnostic tools and treatment strategies for movement disorders.